The study of MO removal over the ZnAl adsorbents prepared by hydrothermal and co-precipitation methods - Yu Shen-Wei; Yang Chia-Hsiang; Wang Chen-Bing (E3S Web of Conferences)
Removal of dye during wastewater pretreatment is both challenging and attractive due to the stability of the dye and its interaction with the adsorbent. In this study, the anionic methyl orange (MO) was selected as model dye, and ZnAl layered double hydroxides (LDHs) prepared by co-precipitation (C) and hydrothermal (H) methods were utilized as adsorbents for the removal of MO dye. ZnAl(H) shows a better adsorption capability of 483 mg/g at pH 3 with a higher BET specific surface area and larger interlayer spacing than ZnAl(C), and it maintains 95% removal efficiency after five cycle durability tests.